2019
DOI: 10.2134/agronj2018.07.0481
|View full text |Cite
|
Sign up to set email alerts
|

Maize Yield Response to Nitrogen Rates and Sources Associated with Azospirillum brasilense

Abstract: New studies are needed to optimize the nitrogen amount that can be applied to utilize the Azospirillum brasilense benefits in maize cropping systems. In addition, information regarding the interaction between the urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT) and biological nitrogen fixation (BNF) and how they affect the crop development and yield is also needed. The objective of this study was to evaluate the effect of rates and sources of N in combination with A. brasilense, on leaf chlorophyll … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 54 publications
3
34
0
3
Order By: Relevance
“…The increase on PUE and corn yield as a function B. subtilis and A. brasilense inoculation compared to control was, on average, equivalent to 100.5 and 54.6% for PUE and 17.4 and 12.8% for grain yield, respectively, regardless of P 2 O 5 application rates. Similar results with B. subtilis and A. brasilense inoculation were reported with greater corn yield between 3.8 to 34% in inoculated plants compared with non-inoculated plants (Kuan et al, 2016;Müller et al, 2016;Traoré et al, 2016;Ahmad et al, 2019;Galindo et al, 2019b).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The increase on PUE and corn yield as a function B. subtilis and A. brasilense inoculation compared to control was, on average, equivalent to 100.5 and 54.6% for PUE and 17.4 and 12.8% for grain yield, respectively, regardless of P 2 O 5 application rates. Similar results with B. subtilis and A. brasilense inoculation were reported with greater corn yield between 3.8 to 34% in inoculated plants compared with non-inoculated plants (Kuan et al, 2016;Müller et al, 2016;Traoré et al, 2016;Ahmad et al, 2019;Galindo et al, 2019b).…”
Section: Discussionsupporting
confidence: 75%
“…under different weather and soil conditions, concluded that crop yield can increase up to 30% with inoculation (Fukami et al, 2016). Also, positive results in corn development and yield has been reported with Azospirillum brasilense inoculation (strains Ab-V5 and Ab-V6) under tropical conditions (Martins et al, 2018;Oliveira et al, 2018;Galindo et al, 2019b). However, greater responses with other PGPB can be achieved (Pankievicz et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…viciae NGB-FR 12646.8–81.4Youseif et al (2017) R. leguminosarum sv . vicieae NSFBR-30 and HUFBR-155–75Argawa and Mnalku (2017)Maize Azospirillum brasilense Ab-V5 and Ab-V627Hungria et al (2010) A. brasilense Ab-V529Ferreira et al (2013) A. brasilense Ab-V5 and Ab-V614.3Galindo et al (2019) Pseudomonas fluorescens 29–31Sandini et al (2019)Wheat Bacillus polymyxa Bp 431713.6–19.5Rodriguez-Caceres et al (1996b) A. brasilense Sp24614.7Ozturk et al (2003) A. brasilense Ab-V5 and Ab-V631Hungria et al (2010) A. brasilense 18Karimi et al (2018)Rice Burkholderia vietnamiensis TVV7522Tran et al (2000) B. vietnamiensis MGK312.1Govindarajan et al (2007)Tomato A. brasilense Sp-711Alfonso et al (2005) P. fluorescens SS557Ahirwar et al (2015)Co-inoculation…”
Section: Inoculants Containing Mixes Of Bacteriamentioning
confidence: 99%
“…These are commercial strains used in Brazil with brand name AzoTotal 1 . These strains when used under similar conditions (Brazilian Savannah) have shown positive results in maize development [2,8,13,16]. Seeds were inoculated one hour before planting and after seed treatment with fungicide and insecticide when the seeds were completely dry.…”
Section: Plos Onementioning
confidence: 99%
“…Maize (Zea mays L.) is among of the most relevant and cultivated grain crop used for human and animal consumption [1]. In Brazil, the average yield (e.g., 5,476 kg ha -1 ) is still low compared with high yielding areas of the USA (USDA average 10,840 kg ha -1 ) and Europe (Eurostat average 8,399 kg ha -1 ) [2][3][4][5], despite technological improvements in plant nutrition, soil management and field equipment. This low maize yield observed in Brazil is usually attributed to low-fertility soils that require high fertilizer inputs for optimum productivity [6].…”
Section: Introductionmentioning
confidence: 99%